Surface Modification of Bentonite with Polymer Brushes and Its Application as an Efficient Adsorbent for the Removal of Hazardous Dye Orange I - Wenjuan Guo; Ahmad Umar; Yankai Du; Luyan Wang; Meishan Pei (Nanomaterials, 2020)
Poly(2-(dimethylamino)ethyl methacrylate)-grafted bentonite, marked as Bent-PDMAEMA, was designed and prepared by a surface-initiated atom transfer radical polymerization method for the first time in this study. Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM) and thermal gravimetric analysis (TGA) were applied to characterize the structure of Bent-PDMAEMA, which resulted in the successful synthesis of Bent-PDMAEMA. As a cationic adsorbent, the designed Bent-PDMAEMA was used to remove dye Orange I from wastewater. The adsorption property of Bent-PDMAEMA for Orange I dye was investigated under different experimental conditions, such as solution pH, initial dye concentration, contact time and temperature. Under the optimum conditions, the adsorption amount of Bent-PDMAEMA for Orange I dye could reach 700 mg·g−1, indicating the potential application of Bent-PDMAEMA for anionic dyes in the treatment of wastewater. Moreover, the experimental data fitted well with the Langmuir model. The adsorption process obeyed pseudo-second-order kinetic process mechanism.